2011
DOI: 10.1021/la202792g
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Adsorption of Proteins on Glass Capillary Surfaces Using Electrospray-Differential Mobility Analysis

Abstract: We quantify the adsorption and desorption of a monoclonal immunoglobulin-G antibody, rituxamab (RmAb), on silica capillary surfaces using electrospray-differential mobility analysis (ES-DMA). We first develop a theory to calculate coverages and desorption rate constants from the ES-DMA data for proteins adsorbing on glass capillaries used to electrospray protein solutions. This model is then used to study the adsorption of RmAb on a bare silica capillary surface. A concentration-independent coverage of ≈4.0 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…On the other hand for IgM desorption from bare silica is 0.004 ± 0.0025 min -1 and 0.00035 ± 0.00007 min -1 for monomers and dimers respectively. These values are well within the wide range of desorption rate constants (≈10 -4 min -1 to ≈1 min -1 ) found in the literature [120,[144][145][146]. Clearly, there are two important inferences: the monomer desorbs faster than the dimer for both surfaces, and the propensity for both the monomers and dimers of IgM to stay adsorbed on the gelatin-passivated surface is lower.…”
Section: N Desg Mt(i) With N Desg Dt(i) N Desl Mt(i) With N Dsupporting
confidence: 86%
See 1 more Smart Citation
“…On the other hand for IgM desorption from bare silica is 0.004 ± 0.0025 min -1 and 0.00035 ± 0.00007 min -1 for monomers and dimers respectively. These values are well within the wide range of desorption rate constants (≈10 -4 min -1 to ≈1 min -1 ) found in the literature [120,[144][145][146]. Clearly, there are two important inferences: the monomer desorbs faster than the dimer for both surfaces, and the propensity for both the monomers and dimers of IgM to stay adsorbed on the gelatin-passivated surface is lower.…”
Section: N Desg Mt(i) With N Desg Dt(i) N Desl Mt(i) With N Dsupporting
confidence: 86%
“…As one of the peer reviewers pointed out: "The systematic study undertaken of the phenomenon is of considerable interest, as it establishes a relatively powerful method for protein adsorption 174 studies." The reviewer in this case was referring to section 4.1 which was published in Langmuir [144]. Section 4.2 extended this to oligomeric proteins.…”
Section: Review Of Es-dmamentioning
confidence: 99%
“…In these experiments, the coverage of RmAb adsorbed on 60 nm PSL nanoparticles as a function of pH was determined using ES-DMA–APM (Supporting Information S4, Figure S2). The coverage reaches a maximum at pH ≈ 8.5 which is close to the isoelectric point (pI) of RmAb . There are at least two possibilities that may explain the maximum coverage near the pI: (i) net zero charge of a RmAb molecule would mean the decreased electrostatic repulsions between neighboring molecules allows for more compact packing on the surface and (ii) the RmAb molecules interact with each other and the PSL surface through hydrophobic interactions; denature significantly; and promote nonspecific adsorption of more RmAb molecules, creating multiple layers.…”
mentioning
confidence: 99%
“…We have found that different IgGs tend to adsorb to the capillary walls of the ES capillaries, which is problematic because it leads to a time‐variant size distribution and may affect quantification of different oligomers,30 but can be significantly reduced by passivating the capillaries with gelatin. Prior to ES of protein samples, 0.5–1.0 mol/L H 2 SO 4 , deionized (18 MΩ/cm) ultrapure water, and 20 mmol/L ammonium actetate buffer solutions were eluted sequentially for 20–30 min through 25‐µm fused silica capillaries (TSI Inc.).…”
Section: Methodsmentioning
confidence: 99%